Comparison of Ischemic Stroke Outcomes and, Patient and Hospital Characteristics by Race/Ethnicity and Socioeconomic Status - Hanchate, Amresh D. (2013)
BACKGROUND AND PURPOSE: Current literature provides mixed evidence on disparities by race/ethnicity and socioeconomic status (SES) in discharge outcomes following hospitalization for acute ischemic stroke. Using comprehensive data from eight states, we sought to compare inpatient mortality and length of stay (LOS) by race/ethnicity and SES. METHODS: We examined all 2007 hospitalizations for acute ischemic stroke in all non-Federal acute care hospitals in AZ, CA, FL, MA, NJ, NY, PA and TX. Population was stratified by race/ethnicity (non-Hispanic Whites, non-Hispanic Blacks and Hispanics) and SES, measured by median income of patient zip code. For each stratum we estimated risk-adjusted rates of inpatient mortality and longer LOS (> median LOS). We also compared the hospitals where these subpopulations received care. RESULTS: Hispanic and Black patients accounted for 14 and 12 percent of all ischemic stroke admissions (N=147,780) respectively and had lower crude inpatient mortality rates (Hispanic=4.5%, Blacks=4.4%; all p-values < 0.001) compared to White patients (5.8%). Hispanic and Black patients were younger and fewer had any form of atrial fibrillation. Adjusted for patient risk, inpatient mortality was similar by race/ethnicity, but was significantly higher for low area-income patients than that for high area-income patients (Odds Ratio=1.08, 95% confidence interval=[1.02, 1.15]). Risk-adjusted rates of longer LOS were higher among minority and low area-income populations. CONCLUSIONS: Risk adjusted inpatient mortality was similar among patients by race/ethnicity but higher among patients from lower income areas. However, this pattern was not evident in sensitivity analyses including the use of mechanical ventilation as a partial surrogate for stroke severity.